Uji Toksisitas Ekstrak Etanol 96% Daun Mahkota Dewa (Phaleria Macrocarpa) dengan Metode Brine Shrimpe Lethality Test (BSLT) - Larysa Fernenda; Kony Putriani; Oksi Apriliani (LPPM Universitas Abdurrab, 2024)
Mahkota dewa (Phaleria macrocarpa) is a plant from the Thymelaeceae family. This plant contains several active compounds such as alkaloids, flavonoids, steroids, saponins, and tannins, so it has potential as a herbal medicine in Indonesia. This study aims to determine the toxicity of the leaves of the god crown using the Brine Shrimp Lethality Test (BSLT) method. Extraction of the god crown leaves using 96% ethanol solvent with the maceration method was then carried out a phytochemical screening which showed that the sample of the crown god leaf contained alkaloids, flavonoids, steroids, saponins and tannins. Toxicity testing of the ethanol extract of Mahkota Dewa leaves on Artemia salina Leach larvae was divided into 5 test groups, namely 4 treatment groups (concentrations of 250 ppm, 500 ppm, 750 ppm, and 1000 ppm) and 1 control or comparison group (seawater). Each concentration was made in 3 vials including 10 Artemia salina Leach larvae. Observations were made by looking at the death of Artemia salina Leach larvae after 24 hours of treatment. The research results can be seen through probit analysis by calculating the LC50 value. The LC50 value of the ethanol extract of Mahkota Dewa leaves was 7,7090 /mL. This shows that the ethanol extract of Mahkota Dewa leaves has a toxic effect on Artemia salina Leach larvae because the LC50 value is <1000 ppm.